1996
DOI: 10.1161/01.res.79.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid–Induced Mitogenic Signaling in Vascular Smooth Muscle Cells

Abstract: As an initial step in testing the hypothesis that high oleic acid concentrations contribute to vascular remodeling in obese hypertensive patients by activating protein kinase C (PKC), the effects of oleic acid on primary cultures of rat aortic smooth muscle cells (RASMCs) were studied. Oleic acid, an 18-carbon cis-monounsaturated fatty acid (18:1 [cis]), from 25 to 200 mumol/L significantly increased [3H]thymidine uptake in RASMCs with an EC50 of 41.0 mumol/L and a maximal response of 196 +/- 15% of control (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 48 publications
5
66
1
1
Order By: Relevance
“…In short, it has been shown (Rao et al, 1995) that a weak increase in DNA synthesis and a moderate increase in VSMC number occur after a 96 h incubation with 20 mM linoleic acid. Similarly, others (Lu et al, 1996; have found that oleic acid at concentrations from 25 ± 200 mM signi®cantly increased [ 3 H]-thymidine uptake and cell number in rat VSMC after a 6 day stimulation period. Furthermore, it has been shown that linoleic acid (50 mM) induced a signi®cant increase in VSMC DNA synthesis and cell number over a 4 day incubation period (Hu et al, 1998).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…In short, it has been shown (Rao et al, 1995) that a weak increase in DNA synthesis and a moderate increase in VSMC number occur after a 96 h incubation with 20 mM linoleic acid. Similarly, others (Lu et al, 1996; have found that oleic acid at concentrations from 25 ± 200 mM signi®cantly increased [ 3 H]-thymidine uptake and cell number in rat VSMC after a 6 day stimulation period. Furthermore, it has been shown that linoleic acid (50 mM) induced a signi®cant increase in VSMC DNA synthesis and cell number over a 4 day incubation period (Hu et al, 1998).…”
Section: Introductionsupporting
confidence: 55%
“…There are contradictory ®ndings regarding the e ects of free fatty acids on VSMC growth. Some investigators have observed growth stimulation (Hu et al, 1998;Lu et al, 1996;Rao et al, 1995) while others suppression (Huttner et al, 1977;Olsson et al, 1999). In short, it has been shown (Rao et al, 1995) that a weak increase in DNA synthesis and a moderate increase in VSMC number occur after a 96 h incubation with 20 mM linoleic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 In vitro studies have reported that unsaturated NEFAs, including oleic and linoleic acid, can directly activate the typical and atypical isoforms of protein kinase C (PKC) in various cell types, including VSMCs. [55][56][57][58] Among other deleterious effects on human vasculature, PKC has been shown to play a central role in mitogenic processes in VSMCs. 59,60 Several studies have clearly shown that NEFAs induce proliferation of VSMCs via PKC activation, [55][56][57] implicating a potential involvement of plasma NEFA elevation in vascular remodelling and hypertension in obese subjects.…”
Section: Possible Trophic Actions Of Nefasmentioning
confidence: 99%
“…[55][56][57][58] Among other deleterious effects on human vasculature, PKC has been shown to play a central role in mitogenic processes in VSMCs. 59,60 Several studies have clearly shown that NEFAs induce proliferation of VSMCs via PKC activation, [55][56][57] implicating a potential involvement of plasma NEFA elevation in vascular remodelling and hypertension in obese subjects. In addition, oleic and linoleic acid were reported to increase the trophic action on VSMC of other growth factors, for example insulin-like growth factor-1 (IGF-1).…”
Section: Possible Trophic Actions Of Nefasmentioning
confidence: 99%